1998
DOI: 10.1074/jbc.273.37.23750
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Regulates Phospholipase Cγ-mediated Calcium Signaling

Abstract: It has been demonstrated that the lipid products of the phosphoinositide 3-kinase (PI3K) can associate with the Src homology 2 (SH2) domains of specific signaling molecules and modify their actions. In the current experiments, phosphatidylinositol 3,4,5-trisphosphate (PtdIns-3,4,5-P 3 ) was found to bind to the C-terminal SH2 domain of phospholipase C␥ (PLC␥) with an apparent K d of 2.4 M and to displace the C-terminal SH2 domain from the activated platelet-derived growth factor receptor (PDGFR). To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
185
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(200 citation statements)
references
References 28 publications
14
185
0
1
Order By: Relevance
“…Recruitment of PLC-g1 to the membrane by PI 3,4,5 P 3 (PIP3), produced by the action of PI3Ks, has been shown to have a function in PLC-g activation (Falasca et al, 1998;Rameh et al, 1998;Maffucci and Falasca, 2007). In agreement with the literature, we detected PI3K activation in BCR-ABL-positive K562 cells (Supplementary Figure 2, right).…”
Section: Resultssupporting
confidence: 91%
“…Recruitment of PLC-g1 to the membrane by PI 3,4,5 P 3 (PIP3), produced by the action of PI3Ks, has been shown to have a function in PLC-g activation (Falasca et al, 1998;Rameh et al, 1998;Maffucci and Falasca, 2007). In agreement with the literature, we detected PI3K activation in BCR-ABL-positive K562 cells (Supplementary Figure 2, right).…”
Section: Resultssupporting
confidence: 91%
“…PI 3-kinase is required for volume recovery after hepatocellular swelling (27), but it is uncertain whether it is involved in swelling-mediated PLC␥ activation. Specifically, activation of PLC␥ by PI 3-kinase appears to be independent of tyrosine phosphorylation (26); yet tyrosine phosphorylation of PLC␥ was seen in the present study. Thus, regulators of PLC␥ other than PI 3-kinase warrant consideration.…”
Section: Discussionmentioning
confidence: 42%
“…The influence of PIP 3 on the PLC-γ1 activity has been looked at more closely. In these reports, the investigators suggested that PIP 3 recognized the C-terminal SH2 domain of PLC-γ1 in vitro (Bae et al, 1998;Rameh et al, 1998). Moreover, they demonstrated that inhibition of the PI-3K activity using a specific inhibitor could attenuate PLC-γ1 activation (Bae et al, 1998;Rameh et al, 1998).…”
Section: Other Activation Mechanismsmentioning
confidence: 99%
“…The N-terminal SH2 domain of PLC-γ1 is known to play a major role in the association with the activated growth factor receptor, while the C-terminal SH2 domain is considered to play a minor role (Chattopadyay et al, 1999;Poulin et al, 2000). However, recently, it has been reported that the C-terminal SH2 domain of PLC-γ1 is involved in interactions with synaptojanin (Ahn et al, 1998), the actin-cytoskeleton (Pei et al, 1996), PIP 3 (Bae et al, 1998;Rameh et al, 1998) and FAK (Zhang et al, 1999). These observations suggest that the two SH2 domains of PLC-γ1 are dissimilar and may mediate the recognition of specific phosphorylation sites.…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%